Une image sur pierre d’un château en bois : un graffiti médiéval au château de Caen - Edward Impey (Archéologie Médiévale)
In the collection of the Musée de Normandie is a loose ashlar block, used or re-used in the annexes built around the 12th-century donjon of the castle at Caen by Phillip Augustus, bearing a remarkable incised drawing of the early 13th century. The composition and the careful detailing imply an experienced draftsman and one familiar with structural techniques. Its importance lies in its subject – a timber castle, or part of one - and in the details of its elevation and construction, rarely illustrated at the time or available from archaeological evidence. The drawing shows a ringwork or, more probably, a motte, its slopes perhaps revetted in timber, crowned with a timber curtain wall, reached by a bridge of unusual form through a massive cross-braced gate-tower. Within, what is probably an aisled hall. The inclusion of a builders’ hoist, apparently in use, adds an additional aspect to its interest.